Kajian Teologis Tentang Cara Orang Tua Mendidik Anak Dalam Keluarga Kristen - Atrina Waruwu (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The family is an institution formed by God on this earth, but often believers do not involve God in their household when problems arise in the family. Parents should educate their children gently, but there are parents who educate their children in a harsh tone. Christian parents educate their children based on the word of God, but there are parents who educate their children not based on the word of God. Parents should educate their children with love, but there are parents who educate not based on love, and often even embarrass their children in public. Educating children in the family has a target to glorify God, but there are parents who don't understand that. The purpose of this research is to find out the theological studies on how parents educate their children in Christian families. The methodology used in this research is qualitative with a library research approach to find articles that are relevant to the topic of discussion. The results of this research are educating with good examples, educating with faith, educating with love, educating patiently, educating meekly, educating humbly, educating by not being angry and educating by forgiving. As a conclusion from this research, parents need to set a good example, through faith, love, patience and gentleness.